2018
DOI: 10.1136/acupmed-2016-011327
|View full text |Cite
|
Sign up to set email alerts
|

Intersubject Synchronisation Analysis of Brain Activity Associated with the Instant Effects of Acupuncture: An Fmri Study

Abstract: The ISS analysis considered the sustained effect of acupuncture and uncovered additional information not shown by GLM analysis. We suggest that ISS may be a suitable approach to investigate the brain responses associated with the instant effects of acupuncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…To our knowledge, this is the first study to explore the differences between instant and sustained effect of head acupoint in depression. Acupuncture treatment produces both instant and sustained effects, [16][17][18] our study indicated that EA at GV20 could first instantly activated bilateral postcentral gyri, right calcarine gyrus, right cuneus. The bilateral postcentral gyri was the hub in the somatosensory network, which identified by early functional connectivity studies.…”
Section: Discussionmentioning
confidence: 61%
“…To our knowledge, this is the first study to explore the differences between instant and sustained effect of head acupoint in depression. Acupuncture treatment produces both instant and sustained effects, [16][17][18] our study indicated that EA at GV20 could first instantly activated bilateral postcentral gyri, right calcarine gyrus, right cuneus. The bilateral postcentral gyri was the hub in the somatosensory network, which identified by early functional connectivity studies.…”
Section: Discussionmentioning
confidence: 61%
“…Comparisons between ReHo and ALFF values (effective acupuncture versus. sham acupuncture sessions) were performed using the paired sample t test (Jin et al., 2018; Qiu et al., 2012; Zhu et al., 2015). Significance was indicated by p = .001 at the voxel level (uncorrected) and p < .05 at the cluster level (family‐wise error correction).…”
Section: Methodsmentioning
confidence: 99%
“…We attempted to explore the involved cerebral areas by comparing the changes of ReHo and ALFF values between posteffective acupuncture and postsham acupuncture. For the aim of this study to explore the cerebral changes induced by acupuncture on SP3, we selected unilateral acupuncture on the right side (relevant to the dominant hemisphere) according to the experimental design of the previous studies (Jin et al., 2018; Qiu et al., 2012). We believed that the findings in the present study will be useful to further understand the effects of acupuncture on the SP3 point on different cerebral areas.…”
Section: Introductionmentioning
confidence: 99%
“…One of the focuses of this research is tbfMRI employed to explore the changes in brain activation during the acupuncture stimulation or a period after stimulation [28][29][30][31][32][33] . These studies last for a shorter time taking healthy volunteers or patients as subjects.…”
Section: De Nitions and Conceptsmentioning
confidence: 99%
“…A small number, one or two, of acupoints are selected in these studies, and a one-time acupuncture administration is given in one experimental program. These studies usually aim to discuss the instant effects [31] and sustained effects [32] of acupuncture. According to the theory of TCM, acupuncture may induce long-lasting post-administration effects [33] .…”
Section: De Nitions and Conceptsmentioning
confidence: 99%